2022
DOI: 10.1002/ijgo.14164
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of risk factors of de novo urinary stress incontinence after cystocele repair: A retrospective cohort study

Abstract: The contents of this page will be used as part of issue TOC only. It will not be published as part of main article.Levator avulsion is a risk factor for de novo urinary stress incontinence after transvaginal mesh surgery for cystocele repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…In order to get more evidence of relationship between levator avulsion and SUI, we started to collect data of patients suffered from levator avulsion who also performed TVM for cystocele repair. Previous data showed levator avulsion may cause de novo SUI after TVM, no matter unilateral avulsion or bilateral avulsion [27]. After we increasing sample size and more women suffered from bilateral avulsion were recruited, the results seemed different.…”
Section: Discussionmentioning
confidence: 84%
“…In order to get more evidence of relationship between levator avulsion and SUI, we started to collect data of patients suffered from levator avulsion who also performed TVM for cystocele repair. Previous data showed levator avulsion may cause de novo SUI after TVM, no matter unilateral avulsion or bilateral avulsion [27]. After we increasing sample size and more women suffered from bilateral avulsion were recruited, the results seemed different.…”
Section: Discussionmentioning
confidence: 84%
“…Recent simulations performed using pelvic magnetic resonance imaging revealed that weakening of either the pubococcygeus or puborectalis muscles caused a shift in the urethral axis, representing a decrease in pelvic floor support, 32 which supports our conclusion. One study confirmed that LAM avulsion is a risk factor for de novo SUI after transvaginal mesh, and the relative risk ratio of de novo SUI with unilateral and bilateral LAM avulsion was 2.23 (95% CI: 1.35-3.68) and 3.12 (95% CI: 1.46-6.67), respectively, 33 warning us of the consequences of ignoring the LAM.…”
Section: Discussionmentioning
confidence: 96%
“…Previous data showed levator avulsion may cause de novo SUI after TVM, no matter unilateral avulsion or bilateral avulsion. 19 After we increasing sample size and more women suffered from bilateral avulsion were recruited, the results seemed different. RR ratio showed only unilateral avulsion related to de novo SUI, which is in accordance with the results we presented before.…”
Section: Discussionmentioning
confidence: 98%